2003
DOI: 10.1081/jdi-120022554
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulopathy in Kuwait: The Spectrum over the Past 7 Years

Abstract: There are few studies that examine, prospectively, the epidemiological profile of glomerulopathy (GP) and its clinicopathological correlation. All patients referred to Al-Amiri renal center in Kuwait from January 1st, 1995 to December 31st, 2001 were screened for GP. Detailed clinical data were collected and serological markers were done. Renal biopsy was performed whenever indicated. During those 7 years, a total of 584 patients were diagnosed, on histological basis, to have GP, 315 of whom were Kuwaiti natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
1
7
1
Order By: Relevance
“…Descriptions of the studies are given in Most of the other studies were prospective, reporting rates from 0.2 /100 000 /year to 2.8 /100 000/year (26, 13,18,19,21,27,43); the retrospective studies reported a similar range of rates, from 0.4 /100 000/year to 2.9 /100 000/year (9,11,14,20,29,30,35,36,38,39). Two studies reported incidence rates of 5.0/100 000/year (28) and 5.7/100 000 /year in males (11) Membranoproliferative glomerulonephritis: thirteen studies were retrospective and six were prospective; the range of incidence rates in all studies was between 0.14 /100 000/year and 0.93 /100 000/year.…”
Section: Resultsmentioning
confidence: 99%
“…Descriptions of the studies are given in Most of the other studies were prospective, reporting rates from 0.2 /100 000 /year to 2.8 /100 000/year (26, 13,18,19,21,27,43); the retrospective studies reported a similar range of rates, from 0.4 /100 000/year to 2.9 /100 000/year (9,11,14,20,29,30,35,36,38,39). Two studies reported incidence rates of 5.0/100 000/year (28) and 5.7/100 000 /year in males (11) Membranoproliferative glomerulonephritis: thirteen studies were retrospective and six were prospective; the range of incidence rates in all studies was between 0.14 /100 000/year and 0.93 /100 000/year.…”
Section: Resultsmentioning
confidence: 99%
“…In India, MPGN has been reported as the most common pathologic finding, with IgAN and MG getting the lowest ranks [16]. In Kuwait and Bahrain, FSGS had a high prevalence and MG was infrequent [17][18][19]. In a report from Saudi Arabia, mesangiocapillary GN was the most common lesion followed by IgAN and FSGS [20].…”
Section: Discussionmentioning
confidence: 99%
“…By the 3rd decade (tables 2, 3), there appears to be a wide-spread increased prevalence of FSGS in Australia [21], Brazil [30,31], India [34], Kuwait [35], Peru [36], Saudi Arabia [32], the United Arab Emirates [18] and the USA [5,23]. But in the surrounding Asian countries like China [24], Hong Kong [37], Japan [10], Korea [11] and Malaysia [28], the prevalence of FSGS is still relatively low.…”
Section: Resultsmentioning
confidence: 99%
“…The increased prevalence of FSGS has been documented in many countries like Brazil [31], India [42], Kuwait [35], Peru [36], Saudi Arabia [32], the United Arab Emirates [18] and the USA [45] (tables 2, 3). This is related to the increasing number of patients with obesity, diabetes mellitus and smoking habits, a pattern representing the rising affluence in these countries where FSGS represents the changing lifestyle of fast food and unhealthy diets predisposing to diseases like obesity and diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%